PENEGAKAN HUKUM PEMERINTAH DAERAH TERHADAP PABRIK YANG TIDAK BERIZIN DI KABUPATEN PELALAWAN TAHUN 2022 - Fujianti, Annisa; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Law enforcement against unlicensed industrial activities is a crucial aspect of the supervisory function of local governments, particularly in maintaining environmental governance and ensuring compliance with legal regulations. This study aims to analyze the law enforcement efforts undertaken by the Regional Government of Pelalawan Regency against palm oil mills operating without permits in 2022. The research focuses on the forms of law enforcement implemented, the inhibiting factors within the enforcement process, and the impact of such efforts on the existence of illegal palm oil mills in the region. The research uses a descriptive qualitative approach, with data collected through interviews and documentation. The main obstacles identified include overlapping authority among institutions, limited capacity of local law enforcement personnel, weak supervision, and the influence of local political and economic interests. Based on these findings, law enforcement efforts must be improved through local regulatory reforms, strengthening the oversight function, and fostering stronger synergy between government institutions and law enforcement agencies. The results indicate that the Regional Government of Pelalawan Regency has undertaken several measures, such as issuing warning letters, suspending operations, and referring cases to law enforcement bodies. However, the implementation of these enforcement measures has not been optimal due to various challenges, including weak inter-agency coordination, limited human and financial resources, and interference from vested interests. Although regulations concerning business licensing are relatively clear, their enforcement remains ineffective in practice. Keyword :Government Law enforcement, Licensing, Benefit, Justice